G266 Stillbirth prevention – A call for paediatricians to be advocates. (27th April 2016) - Qureshi, ZU; Blencowe, H; Amouzou, A; Calderwood, C; Cousens, S; Flenady, V; Fr…en, JF; Hogan, D; Jassir, FB; Mathai, M; Mathers, C; McClure, EM; et al.
Abstract : Aims: Stillbirths have low priority in global health, despite at least half being preventable with achievable care. Reduction has recently become a priority in the UK, with Department of Health calls to half UK stillbirth rates (SBR) by 2030. These are supported by the RCPCH, with improving fetal health being associated with improved child health. We aimed to estimate the 2015 global burden of stillbirth to help inform policy towards reduction as part of the Lancet Ending Preventable Stillbirth Series . Methods: Available data for stillbirths was reviewed (vital registration, national registries, surveys, literature and an investigator group), generating new national estimates for 195 countries. Analysis of stillbirth risk factors, timings, and the acceleration needed in SBR reduction to meet the Every Newborn Action Plan (ENAP) 2030 target of ≤12 stillbirths per 1000 births in each country by 2030 were undertaken. Results: Date available covered 500 million births from 160 countries. An estimated 2.6 million stillbirths occurred in 2015, with 1.3 million occurring during labour, and ten countries accounting for two-thirds of stillbirths (Figure 1 ). There has been an average annual rate of reduction (ARR) in stillbirth of 2% since 2000, compared to 3% for maternal mortality, and 4.5% for post-neonatal under-5 mortality. To reach the 2030 targets, progress in SBR reduction will have to double (ARR of 4.3%), with even greater progress required in the highest burden settings (Figure 2 ). Stillbirths are strongly linked to poor maternal and fetal health, with potentially modifiable factors identified such as malaria (population attributable fraction (PAF) 8·2%), syphilis (7·7%), obesity (10%), smoking (1.7%), maternal age >35 years (6·7%) and prolonged pregnancy (14.0%). Stillbirths frequently ensue because of fetal growth restrictions and/or preterm labour. Congenital abnormalities only accounted for 7.4% of stillbirths. Conclusions: Preventable stillbirths represent the extreme end of fetal pathology that leads to significant childhood morbidity and mortality. Our new estimates will contribute to efforts to measure progress in SBR reduction worldwide, and inform evidence-based policy to improve child health. Paediatricians are increasingly advocating for stillbirth reduction, with wider benefits in improving neonatal and developmental outcomes from improving prenatal fetal health increasingly clear.